Disintermediation and the role of DMCs: a new management strategy in rural tourism Available to Purchase - Fernández-Villarán Ara, Asuncion; Rivera García, Jorge; Pastor Ruiz, Ricardo (European Journal of Innovation Management, 2026)
Purpose The Internet has encouraged rural tourism experience providers to develop a new management strategy that opts for disintermediation to access the market. In this context, incoming travel agencies (destination management companies [DMCs]), despite the local component, lose capacity to promote the rural tourism. The main question is what kind of relationship between stakeholders would enhance effective intermediation processes between them. The paper examines such constraints and limitations of existing relationships between small local rural tourism producers and DMCs. Design/methodology/approach Using the Basque Country region of northern Spain as a case study, the authors used a mixed qualitative and quantitative methodology based on semi-structured in-depth interviews and an online survey. The data analysis strategy used incorporated descriptive and exploratory factor analysis (EFA). Findings In this research, most of the tourism disintermediation factors identified in previous literature were reinforced when tested in the rural context. The results confirm that power, value, product differentiation, digitisation and stakeholder collaboration are key elements. The value provided in the international segment by DMCs, though, was found to be irrelevant. Originality/value This article contributes to filling a gap in the literature on rural tourism destination management from a holistic view of the destination understanding the business-to-business (B2B) relationship among stakeholders in rural tourism. This paper focuses on those elements that create value for local producers to sell the products through intermediaries and provides a framework for understanding the factors involved in value creation in rural tourism intermediation, which is applicable to further empirical studies and provides interesting managerial implications.
Keywords: rural tourism; DMC; disintermediation; management; digitalisation; stakeholder collaboration